Homeschooling in Chile. Report National Survey Results - Aliaga Castillo, Lester (2017)
In 2014 a survey to gather information about families who practice homeschoolingin Chile took place. They answered 67 families on the reasons that took the valuesthey care, forms of socialization, the sources to develop the curriculum and timemanagement for learning. This work is part of a larger research on home educationin Chile.